Analisis Perbankan Syariah Di Jordan - Angger Gumilang; Fathiya Syahidah Nasution; Syairah Nasution; Khaidar Rahmaini Jamila (CV. ITTC INDONESIA, 2025)
The development of the Islamic banking industry in Jordan has shown steady growth since its inception in 1978, supported by comprehensive regulations and the experienced pioneering financial institutions such as Jordan Islamic Bank. The Islamic banking system in the country offers an alternative financing option rooted in principles of justice, transparency, and prohibition of riba, gharar, and maisir. Although facing challenges such as dominance of conventional banks and low financial literacy among the public, the industry possesses significant opportunities through the development of sukuk instruments, Islamic microfinance, and other innovative Sharia-compliant financial products. Government support, a robust legal framework, and the utilization of digital technology are key factors driving sustainable growth and strengthening the position of the Islamic banking sector in the Middle East region and globally. This study provides an analysis of the industry’s development, regulation, products, as well as the challenges and opportunities faced by the Islamic banking sector in Jordan.